A bifunctional bortezomib-loaded porous nano-hydroxyapatite/alginate scaffold for simultaneous tumor inhibition and bone regeneration - Jiafei Chen; Junru Wen; Yike Fu; Xiang Li; Jie Huang; Xiaoxu Guan; Yi Zhou (Journal of Nanobiotechnology, 2023)
Abstract Treatments of osteolytic lesions due to malignant metastasis remain one of the major clinical challenges. The residual tumor cells after surgical resections and an acidic tumor microenvironment are unfavorable for osteogenic induction. Bortezomib (BTZ), a proteasome inhibitor used in chemotherapy, also has an osteogenic potential in concentration- and Ca2+-dependent manners. In this study, controlled delivery of BTZ in a novel bifunctional scaffold based on nano-hydroxyapatite (nHA) and sodium alginate (SA) nanocomposite, namely BTZ/nHA@SA, has been explored. By smartly adjusting microenvironments, a sustainable release of Ca2+ from nHA could be achieved, which was not only able to cross-link SA but also to regulate the switch between the dual functions of tumor inhibition and bone regeneration of BTZ to promote the osteogenic pathway. The freeze-dried BTZ/nHA@SA scaffold has excellent interconnectivity, is capable to promote the attachment and proliferation of mouse embryonic osteoblast precursor cells, as well as effectively induces breast cancer cell death in vitro. Furthermore, in vivo, studies using a mouse tumor model and a rabbit femoral defect model showed that the BTZ/nHA@SA scaffold could promote tumor ablation, and also enhance bone repair. Therefore, the BTZ/nHA@SA scaffold has unique dual functions of inhibiting tumor recurrence and promoting bone tissue regeneration simultaneously. This smart bi-functional scaffold offers a promising novel approach for oncological treatments by synchronously orchestrating tumor inhibition and tissue regeneration for the repair of neoplastic bone defects.